Prevalence of violence in a clinical sample of adolescent patients visiting a child and adolescent psychiatric outpatient clinic in Nepal - Rampukar Sah; Per Håkan Brøndbo; Jasmine Ma; Ketil Lenert Hansen; Narmada Devkota; Bjørn Helge Handegård; Anne Cecilie Javo (PLoS ONE, 2025)
Background Child violence is a global concern affecting the well-being and development of children and adolescents worldwide. Despite the obvious need, few studies on child violence have been conducted in clinical samples, especially in low- and middle-income countries. Objective The aim of this study was to examine the prevalence of different types of violence in past-year among adolescent psychiatric patients in Nepal. Participants and setting The participants were 810 adolescents aged 11–15, 392 boys and 418 girls, who visited a child- and adolescent psychiatric outpatient unit in Kathmandu during a 12-month period. Methods We used a descriptive, quantitative, cross-sectional design. Data was collected with screening instruments completed by the adolescents themselves. Prevalence rates and range of occurrence of various forms of child violence were computed for both genders. Gender comparisons were conducted using Pearson chi-square tests. Adolescents rated the occurrence in the “rarely”, “sometimes”, “often” or “frequently” categories. Associations between the different forms were examined by Spearman’s correlation test. Results In this study 88% of adolescents had experienced some forms of violence, girls reporting higher prevalence than boys last year. Emotional abuse was the most common. Neglect was reported by 25% of the adolescents, and domestic violence by 40%. Sixty percent of the adolescents had experienced peer aggression. Nearly 75% of the adolescents had experienced polyvictimization and it was higher in girls than boys. Significant correlations were found between several forms of violence, indicating compounded risks. Conclusions The study demonstrates high prevalence of multiple forms of violence among adolescent psychiatric patients, calling for increased awareness of child violence in young patients admitted to mental health institutions in Nepal.